Effect of fiber type and polyethylene film on mechanical properties of ultrasonically bonded multi layer nonwoven fabrics - (:unkn) unknown (Ege Universitesi, 2014)
In this study mechanical properties of the ultrasonically bonded nonwoven fabrics were investigated. For this purpose polypropylene, polyester and polyester-viscose nonwoven fabrics which have three different fabric area densities were obtained. Then nonwoven fabrics were bonded to each other by using ultrasonic sewing machine and two layered structures were produced. Also polyethylene film was placed between two nonwoven fabrics and these three surfaces were bonded by using ultrasonic sewing machine and three layers fabrics were obtained. Tensile strength and elongation at break properties of the 2 and 3 layers structures were investigated and effect of the polyethylene film on the mechanical properties of the 3 layers structures was studied. And higher mechanical properties were obtained from the 3 layers polypropylene-polyethylene film-polypropylene structures.
Keywords: Mechanical properties; Nonwoven fabric; Polyethylene film; Ultrasonic sewing